Merlin cooperates with neurofibromin and Spred1 to suppress the Ras–Erk pathway. (17th December 2020) - Cui, Yan; Ma, Lin; Schacke, Stephan; Yin, Jiani C; Hsueh, Yi-Ping; Jin, Hongchuan; Morrison, Helen
Abstract: The Ras–Erk pathway is frequently overactivated in human tumors. Neurofibromatosis types 1 and 2 (NF1, NF2) are characterized by multiple tumors of Schwann cell origin. The NF1 tumor suppressor neurofibromin is a principal Ras-GAP accelerating Ras inactivation, whereas the NF2 tumor suppressor merlin is a scaffold protein coordinating multiple signaling pathways. We have previously reported that merlin interacts with Ras and p120RasGAP. Here, we show that merlin can also interact with the neurofibromin/Spred1 complex via merlin-binding sites present on both proteins. Further, merlin can directly bind to the Ras-binding domain (RBD) and the kinase domain (KiD) of Raf1. As the third component of the neurofibromin/Spred1 complex, merlin cannot increase the Ras-GAP activity; rather, it blocks Ras binding to Raf1 by functioning as a 'selective Ras barrier'. Merlin-deficient Schwann cells require the Ras–Erk pathway activity for proliferation. Accordingly, suppression of the Ras–Erk pathway likely contributes to merlin's tumor suppressor activity. Taken together, our results, and studies by others, support targeting or co-targeting of this pathway as a therapy for NF2 inactivation-related tumors. Graphical Abstract: